How to use live streaming platforms to elicit impulse purchases of tourism and hospitality products from consumers? - Dan Wang; Ching-Cheng Shen; Jennifer Pasion Loverio (Journal of Open Innovation: Technology, Market and Complexity)
Purpose: This study aims to provide a theoretical foundation and guidance for practitioners by redefining digital strategies in the tourism and hospitality industry. Additionally, factors influencing the buying decisions of live broadcast shoppers for tourism and hospitality products are explored. Design and methodology: To examine the proposed theoretical framework 505 survey questionnaires were collected. Of these 466 were valid and used in the data analysis. Findings: Responses from online survey shows that service convenience significantly impacts impulse buying through perceived value and e-trust. Perceived value and e-trust act as intermediaries for service convenience in impulse buying. While perceived value positively influences destination image, e-trust affects destination image. Originality/value: This study presents a novel theoretical framework linking service convenience and impulse buying, and challenging previous research on destination image and impulse buying.